Pharmacogenomic of LH and its receptor: are we ready for clinical practice? - Alessandro Conforti; Raffaella Di Girolamo; Maurizio Guida; Carlo Alviggi; Livio Casarini (Reproductive Biology and Endocrinology, 2025)
Abstract Luteinizing hormone (LH) is fundamental to support development and reproduction. It acts through a receptor expressed in the gonads, modulating mitogenic, anti-apoptotic, and steroidogenic signals. LH is also marketed as a drug for controlled ovarian stimulation (COS), where it is administered to women to support the action of follicle-stimulating hormone and can lead to specific responses, depending on the individual genetic background. These concepts underline the relevance of a pharmacogenetic approach to COS, in the attempt to optimize clinical outcomes and avoid adverse events. However, knowledge is currently limited by the paucity of clinical studies. This review aims to provide a comprehensive overview of LH and its receptor activity, starting from the description of their molecular pathways from in vitro studies. Data on LH action from in vivo studies were described, as well as the impact of LH and LH/choriogonadotropin (hCG) receptor genetic variants on folliculogenesis and its association with infertility or polycystic ovarian syndrome. Finally, evidence from clinical studies evaluating genetic polymorphisms in the context of assisted reproductive technology treatments and its implications for a pharmacogenomic approach were discussed.